Working cotton - Williams, Sherley Anne 1944-; Byard, Carole M. (San Diego Voyager Books, 1997)
A young black girl relates the daily events of her family's migrant life in the cotton fields of central California.
Caldecott Honor Book
"The text of Working Cotton is based on the poems "the trimming of the feathers"
Keywords: Migrant labor -- Fiction; Cotton picking -- Fiction; Family life -- Fiction; Afro-Americans -- Fiction; Blacks -- Fiction